Yield of diagnostic tests in obese children with an elevated alanine aminotransferase. (December 2015) - Rudolph, Bryan; Rivas, Yolanda; Kulak, Shulamit; Pan, Debra; Ewart, Michelle; Levin, Terry L.; Thompson, John F.; Scharbach, Kathryn
Abstract: Aim: Nonalcoholic fatty liver disease (NAFLD) is associated with obesity and affects roughly 10% of children. However, NAFLD is often diagnosed by exclusion – that is, obese children with an elevated alanine aminotransferase (ALT) are screened for other liver diseases in the absence of a biopsy. This testing is nonstandardized, and professional society recommendations differ. This study examines the yield of testing for disorders other than NAFLD in this patient population. Methods: A retrospective study was performed in 120 obese, asymptomatic, noncholestatic children with an ALT ≥40 U/L and additional diagnostic testing. Results: No patients were found to have Wilson's, hepatitis A, hepatitis B, hepatitis C, cytomegalovirus, alpha‐1 antitrypsin deficiency, autoimmune hepatitis, celiac disease or Epstein–Barr virus. Only one patient (1/120) was identified with definite disease other than NAFLD, which was muscular dystrophy. The positive predictive value of a screening test was 5%, and the specificity was 97%. Of 70 children with an abdominal ultrasound, no significant abnormalities were identified. Conclusion: Extensive testing in asymptomatic, noncholestatic, obese children with an elevated ALT may be of limited diagnostic value and false‐positive tests are likely. Large, prospective studies are needed to help focus the work up in this patient population.